Here are the steps in the correct order for solving the equation \(-2(4x + 8) + 2x = -5x + 10\):
-
Distribute: \[-2(4x + 8) + 2x = -5x + 10\] becomes \[-8x - 16 + 2x = -5x + 10\]
-
Combine Like Terms: \[-8x - 16 + 2x = -5x + 10\] simplifies to \[-6x - 16 = -5x + 10\]
-
Get x-terms together on one side: Add \(5x\) to both sides: \[-6x + 5x - 16 = 10\] which results in \[-x - 16 = 10\]
-
Get constants together on one side: Add \(16\) to both sides: \[-x = 10 + 16\] which simplifies to \[-x = 26\]
-
Solve for x: Multiply by \(-1\): \[x = -26\]
So the correct ordered steps are:
- Distribute
- Combine Like Terms
- Get x-terms together on one side
- Get constants together on one side
- Solve for x